Dynamic evolution of MADS-box genes in extant ferns via large-scale phylogenomic analysis - Zhang, Rui; Zhang, Jiao; Xu, Yue-Xia; Sun, Jun-Mei; Dai, Shao-Jun; Shen, Hui; Yan, Yue-Hong (Frontiers in Plant Science, 2024)
Several studies of MADS-box transcription factors in flowering plants have been conducted, and these studies have indicated that they have conserved functions in floral organ development; MIKC-type MADS-box genes has been proved to be expanded in ferns, however, few systematic studies of these transcription factors have been conducted in non-seed plants. Although ferns and seed plants are sister groups, they exhibit substantial morphological differences. Here, we clarified the evolution of MADS-box genes across 71 extant fern species using available transcriptome, genome, and gene expression data. We obtained a total of 2,512 MADS-box sequences, ranging from 9 to 89 per species. The most recent common ancestor (MRCA) of ferns contained approximately three type Ⅰ genes and at least 5–6 type Ⅱ MADS-box genes. The domains, motifs, expression of type I and type II proteins, and the structure of the both type genes were conserved in ferns as to other land plants. Within type Ⅱ genes, MIKC*-type proteins are involved in gametophyte development in ferns; MIKCC-type proteins have broader expression patterns in ferns than in seed plants, and these protein sequences are likely conserved in extant seed plants and ferns because of their diverse roles in diploid sporophyte development. More than 90% of MADS-box genes are type Ⅱ genes, and MIKCC genes, especially CRM1 and CRM6-like genes, have undergone a large expansion in leptosporangiate ferns; the diverse expression patterns of these genes might be related to the fuctional diversification and increased complexity of the plant body plan. Tandem duplication of CRM1 and CRM6-like genes has contributed to the expansion of MIKCC genes. This study provides new insights into the diversity, evolution, and functions of MADS-box genes in extant ferns.